Sidney Sheldon's the tides of memory - Bagshawe, Tilly; Sheldon, Sidney (William Morrow, 2013)
When long-buried mistakes of her youth begin to resurface, old hatreds are rekindled and Alexia De Vere, the conservative party's newest superstar, finds herself on the brink of losing everything -- her power, her family, and even her own life.